Evaluation of propolis to modify soft denture lining materials, part 1 - Ammar K. AL-Nori; Bassima A. Abdullah; Hamza S. AL-neema (University of Mosul, College of Dentistry, 2011)
Aims to evaluate some properties of temporary soft liner (Bony plus) and permanent soft liner (vertex) before and after adding propolis extracts to it. Materials and methods ethanolic extracts of propolis(ethanolic extract of propolis) was added to temporary soft liner (Bony plus), and glycolic extract of propolis(glycolic extract of propolis) was added to permanent soft liner (vertex), then the volumetric dimensional changes, hardness, water absorption and solubility were evaluate, the total samples were (128). Results showed the presence of significant diffrence in the Hardness, Water absorption and Solubility of the modified soft liners (After adding propolis to it), and there was no significant diffrence in the volume of the soft liners before and after adding propolis.Conclusions the volumetric changes of modified and control group of permanent soft liner (vertex) was no significantly different, The modification type (for both permanent and temporary) of soft liner was significantly softer than the control group along the period of storage (1 month) and the modification type (for both permanent and temporary) of soft liner was significantly have more water absorption and solubility than the control group along the period of storage (1 month).